Long-term results of conservative treatment of Sanders type 4 fractures of the calcaneum A SERIES OF 64 CASES - Gurkan, V.; Dursun, M.; Orhun, H.; Sari, F.; Bulbul, M.; Aydogan, M. (My University, 2011)
A high rate of complications is associated with open reduction and internal fixation of Sanders type 4 fractures of the calcaneum. We assessed the long-term outcome of 83 Sanders type 4 comminuted intra-articular fractures of the calcaneum in 64 patients who underwent non-operative treatment between 1999 and 2005. Each fracture was treated by closed reduction and immobilisation in a long leg cast. Patients were reviewed every three months in the first year, and every six months thereafter. At each visit, the involved ankles were assessed by the American Orthopaedic Foot and Ankle Society (AOFAS) criteria. The degree of fracture healing and the presence of osteoarthritis were assessed.